Respiratory epithelium, production performance and behaviour of formaldehyde-exposed broiler chicks - I., Zulkifli; O., Fauziah; A.R., Omar; S., Shaipullizan (Springer Netherlands, 1999)
Two experiments were conducted to evaluate the effect of formaldehyde vaporization of a hatcher on the tracheal epithelium of chick embryos, and on the production performance and behaviour of commercial broiler chicks. In experiment 1, chick embryos were exposed to 23.5 ppm of formaldehyde vapour during the last 3 days of incubation. Tracheal samples were taken at 0, 6, 30 and 54 h after exposure to formaldehyde and examined by scanning electron microscopy for pathological changes. Observable lesions included excessive accumulation of mucus, matted cilia, loss of cilia and sloughing of the epithelium. The lesions were more severe in chicks exposed for 54 h as compared to those exposed for 6 or 30 h. In experiment 2, 60 chicks that had been exposed to formaldehyde vapour as above and 60 control chicks were used to investigate the effect of formaldehyde fumigation on production performance and behaviour. Formaldehyde vaporization resulted in higher weekly (days 0-6 and 21-27) and total (days 0-41) feed intake and poorer weekly (days 0-6, 7-13, 21-27 and 28-34) and overall (days 0-41) feed conversion ratios. Body weight, mortality and behaviour (eating, drinking, sitting and standing activities) were not affected by formaldehyde fumigation.